Case Report: A New Gain-of-Function Mutation of STAT1 Identified in a Patient With Chronic Mucocutaneous Candidiasis and Rosacea-Like Demodicosis: An Emerging Association - Martinot, Martin; Korganow, Anne Sophie; Wald, Mathieu; Second, Julie; Birckel, Elodie; Mahé, Antoine; Souply, Laurent; Mohseni-Zadeh, Mahsa; Droy, Laure; Tarabeux, Julien; Okada, Satoshi; Migaud, Mélanie; et al. (Frontiers in Immunology, 2021)
Purpose Heterozygous missense STAT1 mutations leading to a gain of function (GOF) are the most frequent genetic cause of chronic mucocutaneous candidiasis (CMC). We describe the case of a patient presenting a new GOF mutation of STAT1 with the clinical symptoms of CMC, recurrent pneumonia, and persistent central erythema with papulopustules with ocular involvement related to rosacea-like demodicosis. Methods Genetic analysis via targeted next-generation sequencing (NGS; NGS panel DIPAI v.1) exploring the 98 genes most frequently involved in primary immunodeficiencies, including STAT1, was performed to identify an underlying genetic defect. Results NGS identified a novel variant of STAT1, c.884C>A (exon 10), p.T295Y, not previously described. This variant was found to be gain of function using an in vitro luciferase reporter assay. Rosacea-like demodicosis was confirmed by substantial Demodex proliferation observed via the microscopic examination of a cutaneous sample. A review of literature retrieved 20 other cases of STAT1 GOF mutations associated with early-onset rosacea-like demodicosis, most with ocular involvement. Conclusion We describe a new STAT1 GOF mutation associated with a phenotype of CMC and rosacea-like demodicosis. Rosacea-like demodicosis appears as a novel and important clinical phenotype among patients with STAT1 GOF mutation.